Dietary Vitamin D in Periodontal Diseases: A Scoping Review of Interventions and Assessments - Rafisa, Anggun; Balafif, Felisha Febriane; Najmi, Nuroh; Kuswandani, Faisal (Sean Institute, 2024)
Vitamin D has gained significant attention for its potential role in periodontal health. This scoping review investigates the evidence on dietary vitamin D interventions and assessments in periodontal diseases, examining their impact on periodontal outcomes and identifying research gaps. Using the PRISMA for Scoping Reviews protocols, data were sourced from PubMed and Scopus, including studies focused on dietary vitamin D interventions in periodontal diseases. Exclusions were non-peer-reviewed articles, reviews, animal studies, and inaccessible full-text articles. A total of 22 studies were included: 11 experimental and 11 observational. Among experimental studies, vitamin D supplementation (n=7) was the most common intervention. Observational studies employed various dietary assessment methods, including 24-hour dietary recall (n=2), food frequency questionnaires (FFQ) (n=3), dietary supplement intake (n=3), and combined methods (n=3). Experimental findings suggest that vitamin D supplementation may enhance periodontal health, particularly when paired with non-surgical treatments. Mixed findings from observational studies and limited research on surgical contexts underscore the complexity of establishing definitive conclusions. These findings emphasize the need for standardized methodologies and further investigation to better understand the role of vitamin D in periodontal health.